Pigmentation Disorders Etiology and Recent Advances in Treatments - Aghaei, Shahin (IntechOpen, 2023)
Skin pigmentation disorder is one of the common skin diseases. In general, skin gets its color from melanin pigment, which is produced by melanocytes in the skin. When these cells are damaged, they can negatively affect melanin production. Pigmentation disorders in the skin are classified as hyperpigmentation and hypopigmentation. Hyperpigmentation appears due to increased melanin in the skin. Typical hyperpigmentation disorders include post-inflammatory hyperpigmentation, melasma, solar lentigines, freckles, and café au lait macules. These conditions are generally benign but can be distressing to patients. Addison's disease and some other endocrine disorders may cause diffuse hyperpigmentation. Hypopigmentation is caused by a decrease in melanin production in the skin. Examples of hypopigmentation include vitiligo, albinism, fungal infections, and post-inflammatory hypopigmentation, for example after burns or psoriasis. The nine chapters in this book discuss the latest clinical and therapeutic findings on the most common skin pigmentation disorders and their effect on patients' quality of life.